The impact of classroom context on learners’ achievement in the post-basic school English curriculum in Burundi - Irambona, Alfred; Syomwene, Anne (Research and Social Study Institute, 2023)
In Burundi, the academic performance in English for post-basic school leavers is wanting. Many researchers attribute poor academic achievement to the quality of teaching but fail to investigate the role the classroom context plays in learners’ academic achievement. This paper is a report of part of a study undertaken in 2023 on evaluating the instructional influences of the post-basic school English curriculum for learners’ achievement in Burundi. The paper specifically reports on the impact of classroom context on learners’ achievement in Burundi's post-basic school English curriculum. The study used a convergent mixed methods design and was guided by Communicative Language Teaching and Social Learning theories. For data collection, learners’ questionnaires, teachers’ interviews, and classroom observations were used. The research participants were sixteen teachers of English and three hundred and thirty post-basic school learners in the second and third years of the languages section in the Bujumbura Municipality. The research participants were selected through stratified and simple random sampling techniques. Data was analysed using descriptive and thematic analyses. The study revealed that teachers provided a welcoming learning atmosphere in their respective classrooms and promoted peer assistance. It was also established that teachers motivated learners to speak English differently, enhancing the learning process. It was revealed that teachers inspired learners in matters of using the English language (mean = 4.29, SD =.883). Moreover, the results showed that the classroom surroundings were generally perceived as noisy (mean = 2.95, SD = 1.327), and most of the classes were overcrowded (mean = 2.81, SD = 1.360). The study established that the classroom learning context greatly influenced learners' academic achievement (mean = 3.405, SD =.5030). The study recommended that the government should improve the classroom context for learners’ optimal academic performance in English.